2020
DOI: 10.1088/1755-1315/492/1/012126
|View full text |Cite
|
Sign up to set email alerts
|

Coconut meal as a feed ingredient and source of prebiotic for poultry

Abstract: The low quality protein of coconut meal, coupled with high fibre content, leads to limited use of this agricultural by-product in the poultry diet. Attempts to maximize the amount of coconut meal included in the broiler feed have been made through amino acids supplementation, enzyme addition and pelleting coconut meal. Among these feed technologies and manipulation, pelleting coconut meal appears to be more powerful in promoting the growth of broiler chickens. The reasons for the improvement of broiler growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…17 Coconut meal also contains various soluble sugars, such as glucose, mannose, galactose and arabinose, 18 dozens of amino acids, and an abundance of minerals and vitamins. 19 These nutrients are a good substrate for mushrooms because they can act as precursors for fungal metabolism. This suggested that coconut meal can be used as a supplementary material to sawdust; therefore, it can enhance the mycelial growth of oyster mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…17 Coconut meal also contains various soluble sugars, such as glucose, mannose, galactose and arabinose, 18 dozens of amino acids, and an abundance of minerals and vitamins. 19 These nutrients are a good substrate for mushrooms because they can act as precursors for fungal metabolism. This suggested that coconut meal can be used as a supplementary material to sawdust; therefore, it can enhance the mycelial growth of oyster mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is an increasing trend in the use of oil cakes to produce substrates that will serve as carbon and nitrogen source in manufacturing biochemicals, including enzymes and antibiotics, through fermentation [ 71 ]. Aside from the extensive studies being conducted to optimize the use of copra meal as an alternative feed ingredient, various researchers are now seeking to explore the utilization of copra mannan for the production of prebiotic manno-oligosaccharides (MOS) for food and feed applications [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Humans, similar to animals, cannot readily digest copra meal due to its high mannan content.…”
Section: Opportunities and Value-added Applicationsmentioning
confidence: 99%
“…Rolinec et al [ 83 ] claimed that coconut oil used as an additive in pig feed could encourage probiotic bacteria to grow, including Bifidobacterium and Lactobacillus spp., demonstrating a positive effect for pig health management. Coconut meal or oil has been used recently as a feed additive in broiler chickens and pigs to improve their immunity and increase their productivity [ 83 , 84 , 85 , 86 ]. Laloučková et al [ 87 ] also revealed a positive antibacterial effect of coconut oil against a pathogenic strain of bovine mastitis-causing bacteria, Streptococcus agalactiae .…”
Section: Antibacterialmentioning
confidence: 99%
“…Despite having adequate amount of protein and carbohydrate, the usage of coconut meal (CM) in poultry diet is still limited due several factors: insufficient lysine and methionine concentrations, highly indigestible non-starch polysaccharide (NSP), and low bulk density [ 86 ]. Earlier works by Eamilao [ 127 ] found that broiler chicks tolerated up to 5% CM inclusion in the diets while Mahadevan et al [ 128 ] showed that laying hens nourished with 20% CM were able to maintain their optimum egg production as compared to the corn-soy fed hens.…”
Section: Effects On Poultrymentioning
confidence: 99%